Comparison of characteristics of bimanual coordinated movements in older adults with frailty, pre-frailty, and robust health - Fujikawa, Shoya; Murata, Shin; Goda, Akio; Sawai, Shun; Yamamoto, Ryosuke; Shizuka, Yusuke; Maru, Takayuki; Nakagawa, Kotaro; Nakano, Hideki (Frontiers in Aging, 2025)
IntroductionDespite the growing concern regarding a potential increase in the number of older adults with frailty owing to an aging global population, the characteristics of bimanual coordination in such older adults remain unclear. This study aimed to compare bimanual coordinated movements among community-dwelling older adults with frailty, pre-frailty, and robust health and identify the specific characteristics of these movements in older adults with frailty.MethodsParticipants were categorized into frail, pre-frail, and robust groups based on Kihon Checklist scores. They performed bimanual coordination tasks in-phase (tapping the thumb and index finger together as fast as possible) and anti-phase (alternating the movement between the left and right fingers), and the task parameters were compared among the groups.ResultsThe total travel distance during the anti-phase task in the frail group was significantly shorter than that in the robust group. However, all three groups showed lower finger dexterity during the anti-phase task than in the in-phase task and the left hand than in the right hand.ConclusionOlder adults with frailty exhibit less movement during bimanual coordination tasks than robust older adults, suggesting that such tasks may be useful tools for assessing frailty.